2006
DOI: 10.1088/1742-6596/36/1/014
|View full text |Cite
|
Sign up to set email alerts
|

Quantum marginal problem and N-representability

Abstract: A fermionic version of the quantum marginal problem was known from the early sixties as N-representability problem. In 1995 it was mentioned by the National Research Council of the USA as one of ten most prominent research challenges in quantum chemistry. In spite of this recognition the progress was very slow, until a couple of years ago the problem came into focus again, now in the framework of quantum information theory. In the paper I give a survey of the recent development.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
475
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(499 citation statements)
references
References 19 publications
8
475
0
2
Order By: Relevance
“…However, this calculation is inconclusive, as the distance to the boundary is of the same order, 8 , as the truncation error [recall (13)]. …”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 3 more Smart Citations
“…However, this calculation is inconclusive, as the distance to the boundary is of the same order, 8 , as the truncation error [recall (13)]. …”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…with ð7Þ i are nonzero to a smaller order, 8 , than the error of spectral truncation, 10 . Together with the comments at the beginning of this section, this shows that the absence of pinned spectra is genuine, rather than an artifact of the truncation.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 2 more Smart Citations
“…Since 1960s, how to characterize this convex set has been a central topic of research in the field of quantum marginal problem and N -representability problem [1][2][3][4][5]. The recent development in quantum information theory has shown that the characterization of the 2-RDMs is a hard problem even with the existence of a quantum computer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%